Determinants of Bank Capital Structure - Nedbailo, Tetiana; Brůna, Karel, 1973-; Szabo, Milan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2020)
This research aims to analyze the determinants of bank capital structure, both from the traditional capital theory and capital requirements perspective, as well as the structure of funding sources in the banking industry. The impact of capital determinants, funding sources and capital regulation on banks’ stability is assessed based on two samples covering six countries (Italy, Spain, and Greece against Germany, Luxemburg, and the Netherlands) during 2008-2018. The goal is to discover if there any divergence in the results for the countries with different banking systems. In the paper methods of econometric and trend analysis are used. Several regression tests are performed, exploring relationships between capital determinants (size, profitability, cost of funding, riskiness) and leverage at the first stage of analysis, and also between different funding sources (deposits and wholesale funding) and banks’ stability. The overall impact of the capital structure regulation is analyzed in the framework of the trend analysis in all countries discussed. The empirical results confirm the statistical significance of traditional capital structure determinants also in the banking industry, and prove both the stability distortion effect of the wholesale funding, and positive impact on the stability capital regulation has.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses